Hypermethylated in cancer 1 (HIC1) suppresses bladder cancer progression by targeting yes‐associated protein (YAP) pathway. Issue 4 (11th November 2018) - Zhou, Xiaoguang; Zhang, Peng; Han, Hu; Lei, Hongen; Zhang, Xiaodong
Abstract: Objectives: Bladder cancer (BCa) is the most common malignant tumor in the urinary system. Growing evidence suggests that as a tumor suppressor gene, hypermethylated in cancer 1 (HIC1) is correlated with various malignancies in the modulation of tumor progression. This study aims to investigate the effect of HIC1 on regulating the proliferation, migration, and invasion of BCa. Methods: Quantitative reverse transcription polymerase chain reaction (qRT‐PCR) and Western blot (WB) were used to evaluate the expression of HIC1 messenger RNA and protein in human BCa tissues and cells. Proliferation, migration and invasion assays, and flow cytometry assay were performed to assess the biological functional role of HIC1 in BCa. Co‐immunoprecipitation (Co‐IP) examined the protein‐protein interaction. The signaling pathways involved in the mode of action of HIC1 in BCa were also investigated. Results: HIC1 was found downregulated in tested samples. Cloning formation assay and cell‐proliferation activity analysis showed that overexpression of HIC1 significantly inhibited the proliferation of BCa cells, while knockdown led to the opposite, namely the promotion of the proliferation. Flow cytometry assay confirmed the arrest of the cell cycle at the G1 phase with overexpression of HIC1 observed. Moreover, HIC1 inhibited migration and invasion of BCa. Co‐IP showed the binding between YAP (yes‐associated protein) and TEAD (TEA domain/transcription enhancer factor family members) as well as the cancerostatic activity of HIC1, partially manifested via its negative regulation of YAP signaling pathway. Conclusions: Our data unprecedently showed that HIC1 was responsible for the inhibition of proliferation, migration, and invasion of BCa via the YAP signaling pathway. These findings suggested that therapeutic strategies regulating HIC1 expression might provide effective treatments for BCa. Abstract : Our data showed for the first time that hypermethylated in cancer 1 (HIC1) is responsible for inhibiting bladder cancer (BCa) proliferation, migration, and invasion through yes‐associated protein signal pathway. These findings suggested that therapeutic strategies regulating HIC1 expression may provide an effective treatment of BCa.